Corporate social responsibility and corporate investments: does research and development intensity matter? - Sari Rahmadhani; Faisal Faisal; Corina Joseph; Indira Januarti (Cogent Business & Management, 2024)
The objective of the study is to investigate the relationship between corporate social and environmental responsibility expenditure, research and development (R&D) intensity, and corporate investment in 47 basic industrial and chemical companies listed on the Indonesian Stock Exchange from 2015 to 2019. The study found a positive correlation between corporate social and environmental responsibility expenditure and R&D intensity and that R&D intensity fully mediates the relationship between corporate social and environmental responsibility expenditure and corporate investment. The results suggest that R&D intensity is crucial in enhancing corporate investment performance. This study contributes to the literature on corporate social and environmental responsibility expenditure, R&D intensity, and investment in emerging markets by providing empirical evidence that R&D intensity plays a key role in boosting corporate investment.
Keywords: 650; Corporate social responsibility; research and development intensity; investment; resource-based view theory; indonesia